See It Before It's Too Late? Last-Chance Travel Lists and Climate Change - McGaurr, L; Lester, L (Peter Lang Inc, 2018)
In an era of rapidly increasing human population and global travel, last-chance tourism is attracting considerable media attention (Dawson, Lemelin, Stewart, & Taillon, 2015). This phenomenon is defined by scholars as commercial tourism that exploits vanishing landscapes or icescapes, and/or disappearing natural and/or social heritage (Lemlin, Dawson, Stewart, Maher, & Lueck, 2010, p. 478). Many last-chance destinations and experiences are ones at risk from climate changepolar bear viewing in Canada, the ice-capped peak of Mount Kiliminjaro in Tanzania, the glaciers of Greenland, and Australias Great Barrier Reef (e.g. Frew, 2008, 2012; Lemelin, Dawson, Stewart, Maher, & Lueck, 2010; Piggott-McKellar & McNamara, 2016).